Relationship between jumping-motion and muscle activity during somersault in trampoline: a case study - Matsushima, M. (Science of Gymnastics Journal, 2023)
This study investigated the relationship between jumping-motion and muscle activity during somersaults on a trampoline. Participants were 10 trampoline athletes (3 high-level and 7 middle-level). As for the protocol, the athletes performed a jump continuation of the jumping tucked backward somersault (Back) and the tucked forward somersault with half twist (Barani) on a trampoline. It was measured using an electromyogram (EMG) and video analysis. The jump was defined as "100 ms before touch" 100 ms before the subject landing on the trampoline bed and "Touch" at the moment of landing and "Lowest" at the moment of going down most and "Take off" at the moment of taking off. They were defined as "Before touch phase" from "100 ms before touch" to "Touch", as "Down phase" from "Touch" to "Lowest", and as "Upward phase" from "Lowest" to "Take off". As a result, the trunk inclination angles of both the high- and middle-levels regarding the Back (middle-level 4.3±1.3°, high-level 7.0±2.4°) and the Barani (middle-level 9.2±1.7°, high-level 9.4±1.7°) during the Lowest phase were forward. There were no significant differences. The EMG amplitude of the rectus abdominis (p < 0.05) during the Upward phase and the erector spinae (p < 0.01) during the Before touch phase were significantly higher at the high-level. The trunk was inclined by using the erector spinae such as the high-level between Before 100ms touch and Lowest. Stabilization of the trunk by the activity of the rectus abdominis was the efficient movement of the lower extremity during the Upward phase.